Potential Inhibition of ACE2 Membrane Protein by Flavone Glycosides for Blocking Entrance of SARS- CoV-2 into the Cells; a Computational Study - Ahsan Ibrahim; Ehtisham Ul Haq (Biology, Medicine, & Natural Product Chemistry, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS- CoV-2), since its emergence in Wuhan city of China in late 2019, had been a dilemma for the global healthcare system. Humongous efforts have been put in ascertaining the effective treatments for attenuation of the spread of corona virus disease (COVID-19) pandemic. The aim of this research study is to probe the potential inhibition of angiotensin converting enzyme 2 (ACE2) membrane protein by well-known flavone glycosides, hence preventing the binding of spike proteins with ACE2 and subsequent prevention of entry of SARS- CoV-2 inside the cells. The molecular docking analysis, for total ten flavone glycosides was carried out, that laid out propitious results in terms of binding energies towards the active residues of ACE2 protein with a range of -9.3 to -7.1 kcal/mol. The molecular dynamics simulation also yielded promising outcomes. The in-silico toxicity analysis of all the potential drug candidates was carried out that revealed that all the compounds were non-toxic and safe. Studies may be required for optimum formulation development using these compounds as a part of drug discovery and development phenomenon. This study may play a vital part in exploration of natural compounds in pharmacotherapy of COVID-19.